MON-158 Rates of Illnesses in Patients with Congenital Adrenal Hyperplasia - Mallappa, Ashwini (J Endocr Soc, 2020)
Background: Classic congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is the most common cause of primary adrenal insufficiency during childhood and patients are at risk for life-threatening adrenal crisis. In a recent study from our group, we reported gastrointestinal and upper respiratory tract infections as the two most common precipitating events for adrenal crises and hospitalizations across all ages. We also reported 11 incidents of life-threatening hypoglycemic events in children, sometimes accompanied by seizures. Objective: To evaluate the annual rates of illnesses in patients with CAH. Methods: We retrospectively reviewed longitudinally collected data over 23 years from 156 CAH patients enrolled in our CAH natural history study (www.clinicaltrials.gov #NCT00250159). Incidence of illnesses and occurrence of stress-dose days were computed per person-years. Incidence rate ratio (IRR) with 95% confidence intervals (CI) were calculated for comparisons. Results: A total of 2298 visits (1909 for children and 389 for adults) were available for evaluation among the 156 patients (21-OHD: 97.4%). A total of 1870 illness events (1664 in children) were observed in 143 patients (121 children) and 2710 stress-dose days (2460 in children) were observed in 141 patients (120 children) during the study period. The incidence rate of illnesses was higher in children than adults (1.5 vs. 0.5 illnesses/person-years, IRR = 3.1, 95% CI 2.7 - 3.6; P<.0001) with incidence highest in young patients: 2.5 illnesses/person-years in <3 year olds. Similarly, the stress-dose days were higher in children than adults (2.2 vs. 0.6 days/person-years, IRR = 3.8, 95% CI 3.3 - 4.3; P<.0001). Conclusions: Patients with CAH do not appear to have higher rates of infectious illnesses than expected, but remain at risk for life-threatening adrenal crises. As expected, illness rates are higher during childhood than adulthood. Prevention of adrenal crisis is crucial and is best accomplished through repeated age-specific education of patients and caregivers. Acknowledgement: This research was supported by the Intramural Research Program at the National Institutes of Health (NIH), Bethesda, Maryland.